Genetic potential of Kazakh White-headed and Hereford breeds for beef production in Purebred farms and crossbreeding (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ibrayeva R, Nurgazy K, Satiyeva K, Gabit G, Mukhametzhanova O. 2025. Genetic potential of Kazakh White-headed and Hereford breeds for beef production in Purebred farms and crossbreeding. Biodiversitas 26: 761-769. Kazakhstan is experiencing essential growth in the livestock sector, with the production of environmentally friendly products serving as a key competitive advantage for the nation. Our study analyzed the meat productivity indices of the Kazakh White-headed and Hereford breeds, along with their hybrids. The investigation focused on assessing the meat quality of Kazakh White-headed and Hereford bulls in different genotype combinations by comparing key meat productivity indices. The meat from the controlled slaughter of test bulls complied with Category I requirements. Carcass weights of Hereford bulls surpassed those of the Kazakh White-headed breed by 42.9 kg (18.1%, P?0.05) and exceeded those of crossbreed bulls by 9.0 kg (3.3%, P?0.05). The Kazakh White-headed breed demonstrated a higher yield of internal fat: internal fat yield varied on average from 2.5% to 3.2% (15 month aged bulls) that depended on the breed: Kazakh White-headed ?3.2%, Hereford ?2.5%, and crossed bulls ? of 2.7%. However, in terms of flesh content, Kazakh White-headed bulls were 43.2 kg (22.5%, P?0.05) lighter than Hereford bulls, and crossbreed bulls were 8.1 kg (3.6%, P?0.05) lighter. In analyzing flesh yield, Kazakh White-headed bulls fell short by 2.4 kg (2.9%) compared to Hereford bulls, which were marginally lower by 0.1 kg (0.1%) compared to crossbreed bulls of the same age. The protein-fat ratio was determined to be 1:0.65 in Kazakh White-headed bulls and 1:0.64 in both Hereford and crossbreed bulls. Profitability was 22% for the Kazakh White-headed breed, 43% for the Hereford breed, and 39% for the crosses of the White-headed and Hereford breeds.
Keywords: Bulls, carcass, genotype, live mass, profitability